Enrofloxacin Pharmaceutical Formulations through the Polymer-Free Electrospinning of β-Cyclodextrin-oligolactide Derivatives - Diana-Andreea Blaj; Cătălina Anișoara Peptu; Maricel Danu; Valeria Harabagiu; Cristian Peptu; Alexandra Bujor; Lăcrămioara Ochiuz; Cristina Gabriela Tuchiluș (MDPI AG, 2024)
Enrofloxacin (ENR), a member of the fluoroquinolone class of antibiotics, is widely used in veterinary medicine to treat bacterial infections. Like many antibiotics, ENR has limited water solubility and low bioavailability. To address these challenges, drug formulations using solid dispersions, nanosuspensions, surfactants, cocrystal/salt formation, and inclusion complexes with cyclodextrins may be employed. The approach described herein proposes the development of ENR formulations by co-electrospinning ENR with custom-prepared cyclodextrin-oligolactide (CDLA) derivatives. This method benefits from the high solubility of these derivatives, enabling polymer-free electrospinning. The electrospinning parameters were optimized to incorporate significant amounts of ENR into the CDLA nanofibrous webs, reaching up to 15.6% by weight. The obtained formulations were characterized by FTIR and NMR spectroscopy methods and evaluated for their antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. This study indicates that the presence of CDLA derivative does not inhibit the antibacterial activity of ENR, recommending these formulations for further development.